Measuring Financial Stress Index for Malaysian Economy - Dahalan, Jauhari; Abdullah, Hussin Bin; Umar, Mohammed (International Journal of Economics and Financial Issues, 2016)
The study measures financial stress index for Malaysian economy. We aggregate the identified financial and economic factors into a single index using the principal component analysis (CPA). The result shows that MFSI increases as a result of increase in banking sector fragility index, credit stress, external debt, stock market volatility and exchange market pressure index. Moreover, the weights of the variables reveal that the magnitude of the Malaysian financial stress is mainly driven by the fragility of the banking sector. The combine variables explain about 53 percent of the total variation in the Malaysian financial stress index (MFSI). Thus, the financial stress is determined to be the key player in the co-movement of the components used in the construction process. Furthermore, the aggregated components practically capture the known key aspects of financial stress in Malaysia. The implication of the finding is that authorities should focus more on banking sector stability than other components of the financial stress. This will help to reduce the overheating of the Malaysian financial stress. Keywords: Economic indicators, financial crisis, financial stress index, Malaysia JEL Classifications: C43, G01